The legal nature of the horizontal regulation, the real estate consumer tutelage and the unfair contractual terms (Prudentia Iuris, 2017)
This essay analizes the legal nature of the Horizontal Regulation, in order to determine, given the existence of unfair contractual terms, that the principles and rules of the consumers protection could be applied to the real legal Estate system. Therefore, we ask ourselves what is an adhesion contract? What characters does it have? And what influence does it have in the Institute indicated? On that basis, it brings up to our attention the real Estate consumer tutelage institute, which gives us a broad defiance to legal regulation, and has a large impact not only among the academic field, but also in society dayto- day life. Lastly, the influence of the good faith principle at the co-property regulation is studied, giving us the starting point to study and exemplify clauses stipulated under which the dominant contract party includes contractual terms that alter or disturb their respective positions, and break the balance of their rights and obligations.
Keywords: Legal nature; Horizontal Regulation; Consumer protection; Real estate consumer; Unfair contractual terms; Contract of adherence